Unbinding the Broken Hearted Biblical and Theological Reflections - Black, Kathy (Journal of religion, disability & health, 2006)
In this article, Biblical texts and the various theologies that guide our congregations' practices are analyzed for the negative and positive influences on the lives of persons with various disabilities. A Theology of Interdependence is posed as a foundation for congregations to be in joint ministry with people who live with a disability.